EFFECTS OF BANDWIDTH AND DELAY ON THE ROUTING INSTABILITY - Abbass, Ghazanfar; Iftikhar, Saman; Asif, Nadeem (European Scientific Journal, ESJ, 2012)
In the current situation, the Internet has proven remarkablyrobust. Underlying advances and upgrades in Internethardware and software infrastructure have forestalled the most serious problems of bandwidth shortages and aperiodic lack of router switching capacity. In this paper weanalyze the affects of bandwidth and delay on the routinginstability, although there are several instabilities in routing. We also suggest the ways to improve routing stability andperform various tests on routing in different ways.We also analyzed 50 sample tests on SPSS and found thatthey have strong significant relationship between dependentand independent variables. We performs test on 16, 32 and64 switches and then evaluated. From these tests on routingwe concluded that delay has negative relation with therouting stability while bandwidth has positive relation with therouting stability. So for better performance and results,increase the bandwidth and decrease the delay.